Political Communication in the Digital Age: The Role of Social Media and Digital Activities in the 2024 Election Campaign - Alkadrie, Najwa Ulfa (Universitas Medan Area, 2025)
Political communication is a complex communication process in which the language and symbols used by leaders, the media, citizens, and groups of citizens influence individuals and society, as well as the public policies of the state, state, or community (Perloff, 2021). Along with the development of technology, political communication activities can currently be carried out through digital media, one of which is social media. An interpretive descriptive analysis with a content analysis method was used in the study to describe the data on digital campaign strategies carried out by political actors on social media during the general election year. The survey results show that political actors use social media as a place to share information, a means of interaction, and viral marketing.